The Effect of Counselor Training Programs on the Quality of Interventions in Schools - Belangi, Siska Putri; Nizam, Zain; Rahman, Rashid; Chai, Nong (Yayasan Adra Karima Hubbi, 2025)
The quality of school counseling interventions is a critical factor in supporting students’ academic, social, and emotional development. Effective counselor training programs are essential for equipping school counselors with the skills and knowledge needed to address diverse student needs. Despite the importance of training, there is limited empirical evidence on the direct impact of such programs on the quality of counseling interventions. This study examines the effect of counselor training programs on intervention quality in schools, focusing on professional competence, intervention outcomes, and counselor confidence. The research aims to evaluate how participation in structured training programs influences the effectiveness of school counselors in delivering interventions. A mixed-methods approach was employed, combining pre- and post-training surveys, in-depth interviews, and observational analysis. The study involved 150 school counselors across 20 schools, with data analyzed using thematic coding and statistical comparison of intervention outcomes. The findings reveal that participation in training programs significantly improves counselors’ confidence and professional competence, leading to enhanced intervention quality. Key improvements were observed in communication skills, problem-solving strategies, and the ability to tailor interventions to individual student needs. The study concludes that investing in counselor training programs has a substantial positive impact on the overall quality of school counseling services.